DAMPAK DARI VERBAL ABUSE TERHADAP KEADAAN PSIKOLOGIS SESEORANG - Maryam Nafisah; Tiara Andiani Alif; Luthfiana Syachfitri; Syahnur Rahman (PSIKOWIPA (Psikologi Wijaya Putra), 2021)
Verbal Abuse is an act of violence that is carried out verbally / verbally, which can cause personal harm, even the worst is suicide by the victim. This study was conducted to investigate the Psychological Impact of Verbal Abuse. In the process, this study used literature studies and surveys to adolescents aged 16 to 25 years, by asking 5 open-ended questions, 2 choice questions, and 9 questions with a scale of 1-4 choices given to 55 respondents. In this study, it showed that verbal abuse had an impact on 65.5% of respondents and had an impact on 35.5% of respondents which was indicated by psychological responses such as anger, sadness, disappointment, fear, anxiety, eating problems, sleep problems, feelings of wanting to hurt yourself, and feelings of self-harm. want to kill myself.